High-precision QEC-value measurement of the superallowed β+ emitter 22Mg and an ab initio evaluation of the A=22 isobaric triplet - Reiter, Moritz Pascal; Drozdowski, Oliver (Physical review, 2017)
A direct QEC-value measurement of the superallowed β+ emitter 22Mg was performed using TRIUMF's Ion Trap for Atomic and Nuclear Science. The direct ground-state to ground-state atomic mass difference between 22Mg and 22Na was determined to be QEC=4781.40(22) keV, representing the most precise single measurement of this quantity to date. In a continued push toward calculating superallowed isospin-symmetry-breaking corrections from first principles, ab initio shell-model calculations of the A=22 isobaric multiplet mass equation are also presented for the first time using the valence-space in-medium similarity renormalization group formalism. With particular starting two- and three-nucleon forces, this approach demonstrates good agreement with the experimental data.